Relevanz und Dimensionen forschungsmethodischer Ausbildung im Fach Deutsch als Fremdsprache und in der internationalen Germanistik - Riemer, Claudia (Linguistik Online, 2025)
This article looks at the global development of demand for German as a foreign language and addresses selected questions about the consequences of these developments for German language education, the training of teachers to teach German and the development of research worldwide. Given the (growing and often insufficiently covered) demand for teachers in many regions of the world, questions arise as to the academic qualifications that future teachers and young researchers will need and the role that knowledge of empirical research methodological should play in academic training in the academic studies in German Studies and German as a foreign language. The perspectives associated with research methodology training are discussed and examples of suitable teaching and learning materials available in the DAAD programme Dhoch3 will be presented.